The Application of Dielectric Barrier Discharge Plasma on Fischer-Tropsch Synthesis: A Review - Teuku Mukhriza; Hartati Oktarina (Fakultas Teknik, 2021)
Fischer-Tropsch (FT) Synthesis has been widely known for centuries as the process of converting syngas to liquid fuels. Several reactors including Slurry bubble column, fluidized-bed, and fixed bed reactors have been used for FTS on an industrial scale. Although science has seen remarkable development in technology for FT synthesis, the industry still faces challenges in optimizations of process parameters and achieved desired selectivity. Extensive research has been continuously conducted to seek the best FT reactor offering heat uniformity and efficient heat transfer across the reactor to increase the catalytic activity and its lifetime. Dielectric Barrier Discharge (DBD) plasma has become one of the options to deal with these issues. This reactor work under low temperature delivers a synergistic effect between plasma and catalyst to break H2 and CO bond. DBD plasma is also suitable for feedstock with high H2/CO molar ratios. It is also found that FT catalyst such as cobalt catalyst used in DBD plasma was well dispersed on the support which in turn favour the selectivity toward liquid hydrocarbon.